Examining the efficacy of a self‐administered report form in missing person investigations. (14th January 2020) - Gabbert, Fiona; Tamonyte, Donata; Apps, Joe; Caso, Alessandra; Woolnough, Penny; Hope, Lorraine; Handscomb, Megan; Waterworth, Georgina
Abstract : Purpose: The success of missing person investigations often centres on the quality of information obtained in the early stages. Reliable information can not only inform the search but might also become vital evidence if the case broadens into a criminal investigation relating to a sexual offence, abduction, or even murder. In addition to eliciting high‐quality information, police officers must consider that those close to the missing person are likely going through a very difficult and stressful time. Across two studies, we developed and tested a self‐administered form (SAI‐MISSING) designed to obtain reliable information that would meaningfully inform a missing person investigation, as well as providing a means for family and friends to be actively involved. Methods: In Experiment 1, 65 participants were tested individually and asked to provide a description of a person they knew well but had not seen for 24 hr. In the second study, 64 participants were tested in pairs, but immediately separated into different rooms and instructed to imagine that the person they came with has gone missing. In both studies, participants completed either the SAI‐MISSING tool, or a self‐administered control form. Results: In Experiment 1, we found that the SAI‐MISSING tool elicited significantly more information regarding physical descriptions and descriptions of clothing and personal effects, than the comparison control form. In Experiment 2, we replicated this finding and further showed that the SAI‐MISSING tool produced higher accuracy rates than the control form. Conclusions: Given the positive outcomes, potential applications of the tool are discussed.